Diagnosing Central Retinal Artery Occlusion (CRAO) without Fundus Examination - Schultheiß, Maximilian; Steinhorst, Nils Alexander; Dippel, Susanne; Spitzer, Martin S.; Poli, Sven; Feltgen, Nicolas (Klinische Monatsblätter für Augenheilkunde, 2021)
In the field of ophthalmology, central retinal artery occlusion is still one of the unsolved pathologies, as there is no widely accepted evidence-based therapeutic concept. Meta-analysis suggests that intravenous fibrinolysis might help to improve the outcome if performed within the first 4.5 hours after symptom onset. However, this short window of opportunity is often missed due to delays during diagnostic testing (e.g. time elapsed before performance of an ophthalmological examination) or patient-processing (referring the patient to a specialized medical facility). This article presents a diagnostic tool in the form of a simple questionnaire, comprising a medical history and examinations, which could help to minimize the time required to initiate the appropriate treatment.
Keywords: central retinal artery occlusion (CRAO); diagnostic tool; REVISION study